Management Strategies of School Principals in Improving Teacher Performance: A Systematic Literature Review - Cahyaningrum, Fadhilah; Subiyantoro, Slamet; Yulisetiani, Septi (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
This study aims to review the management strategies of school principals in improving teacher performance through a Systematic Literature Review (SLR) approach. Articles were collected from Google Scholar and accredited national journal databases using the keywords “principal management strategies”, “school principal leadership”, and “teacher performance”. The inclusion criteria consisted of articles published between 2018 and 2025, written in Indonesian or English, and directly discussing principals’ strategies for improving teacher performance. A total of 20 articles met the criteria and were included in the analysis. The results indicate that principals improve teacher performance through managerial functions, democratic and participatory leadership styles, academic supervision, motivation and reward systems, discipline building, and continuous professional development through training and workshops. Supporting factors include a conducive school climate, adequate facilities, and effective communication, while inhibiting factors consist of limited time, teachers’ resistance to change, and low participation among some teachers. This study recommends strengthening participatory leadership and continuous professional development programs for teachers.